ATTRACTING INVESTMENTS TO THE “GREEN” ECONOMY: RELEVANCE, CHALLENGES, AND SOLUTIONS - Matyakubova Yulduzkxon Bakhromovna (Modern American Journals, 2025)
This study offers a comprehensive assessment of the critical role of investment mobilization in advancing the transition to a “green” economy in light of escalating global environmental challenges and the imperative for sustainable development. The paper explores key financial mechanisms for attracting private and international capital into green sectors, including renewable energy, energy-efficient and environmentally sound technologies, and green infrastructure. It further analyzes systemic barriers to green investment, such as underdeveloped legal and institutional frameworks, limited financial capacity, and insufficient infrastructure. Drawing on international best practices, the study outlines actionable solutions, including the issuance of green bonds, the development of public-private partnerships (PPPs), and enhanced cooperation with international financial institutions. Special attention is given to Uzbekistan’s strategic reforms, regulatory frameworks, and national programs designed to facilitate a low-carbon, resource-efficient, and inclusive economy. The findings underscore the indispensable role of targeted investments in achieving environmental sustainability and long-term economic resilience.
Keywords: Green economy, green investments, renewable energy, financial mechanisms, environmental sustainability, green bonds, sukuk, green certification.